2009
DOI: 10.1111/j.1742-6723.2009.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

White‐eyed blowout fracture: Another look

Abstract: Orbital floor fractures have the potential to cause significant morbidity both in the short and long terms and commonly present to the ED for initial assessment. Although treatment of the majority of these injuries involves clinic review and possible later surgery, there is a specific subset that present to emergency clinically suggestive of a head injury. This subset, 'white-eyed blowout', usually occurring under 18 years of age, with a history of trauma and little sign of soft tissue injury, describes a trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 11 publications
1
20
1
1
Order By: Relevance
“…Orbital floor fractures can present in isolation or in combination with other facial fractures. The etiology is usually direct trauma to the orbital region resulting in fracture to the orbital floor 1 . The fracture pattern is usually an "open door" defect and is typically seen in adults with herniation of the orbital contents into the maxillary sinus.…”
Section: Introductionmentioning
confidence: 99%
“…Orbital floor fractures can present in isolation or in combination with other facial fractures. The etiology is usually direct trauma to the orbital region resulting in fracture to the orbital floor 1 . The fracture pattern is usually an "open door" defect and is typically seen in adults with herniation of the orbital contents into the maxillary sinus.…”
Section: Introductionmentioning
confidence: 99%
“…Ethunandan and Evans reported seven cases of WEBOFs, of which one was a 29-year-old [8]. Mehanna et al reported a 21-year-old man with WEBOF that underwent surgery six days after the injury [9]. This patient continued to have extraocular muscle paresis, despite satisfactory postoperative computed tomography of the maxillofacial bones (CTMF).…”
Section: Reviewmentioning
confidence: 99%
“…Fortunately, oculocardiac symptoms resolved and the patient regained full ocular motility postoperatively. Mehanna et al reported three cases of WEBOF, of which one was initially mistaken for a head injury and another was completely missed [9]. Regrettably, the patient with the missed orbital fracture exhibited persistent extraocular muscle paresis despite adequate surgical reconstruction and no muscle impingement evident on postoperative CTMF.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine neuroradiologische Untersuchung sollte jedoch in jedem Fall bei zusätzlichen Symptomen wie einer Papillenschwellung, Pupillenstörung, Nystagmus oder weiteren neurologischen Symptomen erfolgen (▶ Abb. 2a-c) (21).…”
Section: Therapieunclassified